Leveraging artificial intelligence (AI) technology for enhanced border surveillance at the Malaysia-Thailand land border - Norilyani Md Nor,; Marina Abdul Majid,; Andika Ab. Wahab, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Despite various initiatives taken by the government, Malaysia shows a trend of increasing migrant smuggling. Weaknesses in the border control management have resulted in the escape of smugglers at the border gate. Thus, this article aims to assess the potential application of artificial intelligence (AI) technology at the Malaysia-Thailand land border in enhancing border security. Based on a series of interviews with relevant ministries, enforcement agencies, technology experts, academic experts and other stakeholders, as well as secondary sources, this study found that AI technology has the potential to overcome issues pertaining to weak border control management faced by the Royal Malaysian Police (RMP), the main enforcement agency that manages the Malaysia-Thailand land border along with other enforcement agencies. Among the issues are a lack of enforcement, integrity concerns and limited manpower to control Malaysia’s porous borders. However, some strategies should be taken to adapt AI to our border security system. Thus, this article analyses the concept of Integrated Border Management (IBM) to obtain coordination and cooperation among all relevant authorities and countries involved in the adaptation of AI technology at the Malaysia-Thailand land border. This article also analyses how Malaysia should respond to the ethical implications of AI technology. This study will help promote a cross-border collaboration network between Malaysia and related foreign countries in dealing with migrant smuggling issues.